2022
DOI: 10.1103/physrevd.105.062007
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric imaging of intensely radiating negative leaders

Abstract: The common phenomenon of lightning still harbors many secrets and only recently a new propagation mode was observed for negative leaders. While propagating in this "intensely radiating negative leader" (IRNL) mode a negative leader emits 100 times more very-high frequency (VHF) and broadband radiation than a more normal negative leader. We have reported that this mode occurs soon after initiation of all lightning flashes we have mapped as well as sometimes long thereafter. Because of the profuse emission of VH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…This is typical for LOFAR observed flashes, which suggests that thunderstorms in this region typically have an expansive lower positive charge region. The same lightning flash was also analyzed in previous studies (e.g., Scholten et al., 2021a, 2021b; Scholten, Hare, Dwyer, Liu, et al., 2021; Scholten, Hare, Dwyer, Sterpka, et al., 2021), which focused on, for example, flash development and VHF intense stages termed intensely radiating negative leaders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is typical for LOFAR observed flashes, which suggests that thunderstorms in this region typically have an expansive lower positive charge region. The same lightning flash was also analyzed in previous studies (e.g., Scholten et al., 2021a, 2021b; Scholten, Hare, Dwyer, Liu, et al., 2021; Scholten, Hare, Dwyer, Sterpka, et al., 2021), which focused on, for example, flash development and VHF intense stages termed intensely radiating negative leaders.…”
Section: Resultsmentioning
confidence: 99%
“…Scholten, Hare, Dwyer, Liu, et al. (2021b) found that the structure of the discharge starting at 1 ms or at 3 ms is rather complex. Nearly simultaneous (within 100 μs) VHF sources are distributed in a volume of 1 km 3 , with no easily discernible discharge channels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a large time integration window is used for this case, it is unnecessary to apply the beamforming technique. Except for the baseline and the number of antennas, Cases B and C represent the configuration of the latest LOFAR studies (Scholten et al., 2021b, 2022). The last case represents a moderate increase in the baseline of the interferometer used by Pu and Cummer (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Simulations can provide the constraints on the source parameters in order for the sources to be resolved by a particular instrument. In fact, work is currently underway to simulate LOFAR observations to investigate accuracy and imaging artifacts of the LOFAR interferometry analysis (Scholten et al., 2022).…”
Section: Discussionmentioning
confidence: 99%